2017
DOI: 10.1007/s10067-016-3528-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the choice of first- and second-line biologic therapy for the treatment of rheumatoid arthritis: real-life data from the Italian LORHEN Registry

Abstract: According to international recommendations, the selection of the biologic disease modifying anti-rheumatic drug (bDMARD) for rheumatoid arthritis (RA) is mainly left to the clinician's preference. We analyzed the real-life factors influencing the first-line choice or the switching strategy, focusing on the prescription of abatacept (ABA) or tocilizumab (TCZ) compared to TNFα inhibitors (TNFi). Patients enrolled in the Lombardy Rheumatology Network (LORHEN) Registry after January 1, 2010, when all considered bD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Although there is no consensus on age, infectous risk, and comorbidities that affect the choice of the biological drugs in patients with RA, switching to biological treatments apart from TNFi are also supported for most TNFi insufficient responders. [ 25 , 26 ] Our real life study demonstrated that comorbidties affect the choice of first line biological DMARDs however we couldn’t find significant differences in the choice of second line biological DMARDs and swapping to biological treatments apart from TNFi. Furthermore, there was no significant differences between the groups with or without history of orthopedic surgery regarding the choice of first line and second line biological therapy.…”
Section: Discussionmentioning
confidence: 84%
“…Although there is no consensus on age, infectous risk, and comorbidities that affect the choice of the biological drugs in patients with RA, switching to biological treatments apart from TNFi are also supported for most TNFi insufficient responders. [ 25 , 26 ] Our real life study demonstrated that comorbidties affect the choice of first line biological DMARDs however we couldn’t find significant differences in the choice of second line biological DMARDs and swapping to biological treatments apart from TNFi. Furthermore, there was no significant differences between the groups with or without history of orthopedic surgery regarding the choice of first line and second line biological therapy.…”
Section: Discussionmentioning
confidence: 84%
“…For RA patients with active disease despite conventional DMARDs, current recommendations do not specify a treatment of choice from among approved anti–tumor necrosis factor (anti‐TNF) inhibitors (e.g., adalimumab, certolizumab pegol, etanercept, golimumab, or infliximab) or the non‐TNF options (e.g., abatacept, anakinra, rituximab, sarilumab, tocilizumab, and tofacitinib) in some cases . The choice of biologic therapy for each patient is generally based on consideration of patient‐related factors, disease‐related factors, the mechanism of action of the prescribed medication, and patient preferences for treatment .
A general preference for subcutaneous biologic therapies has previously been reported among rheumatology patients. Results of the current surveys indicate that rheumatoid arthritis patients, including biologic‐naive patients, are generally open to intravenous or subcutaneous treatment. Patients receiving intravenous therapy express high satisfaction with this route of administration.
…”
Section: Introductionmentioning
confidence: 99%
“…The use of bDMARDs in controlling patients with rheumatoid arthritis has revolutionized the evolution of the disease (13). Despite the broad spectrum and the constant development of biological treatment, there is no solid proof for the strategy of choosing the rst bDMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning comorbidities, arterial hypertension was more represented in TCZ group compared to non-TCZ group and the opposite for diabetes that was associated with the non-TCZ group. Monti S et al (13) revealed that age and comorbidities in uence the choice towards ABA and TCZ compared to TNFi. Previous studies indicated that age and the presence of comorbidities are associated with a decreased response by Etanercept (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation